Rozumienie narracyjne w perspektywie interakcjonizmu interpretatywnego, poznania hermeneutycznego i refleksji fenomenologicznej - Krawczyk-Bocian, Amelia (Studia Edukacyjne, 2020)
The conceptual category of the reasoning narrative is the starting point for the considerations presented. Looking at the concept through the prism of interpretative interactionism and the phenomenological and hermeneutic approach helps to discover the meaning and significanceof each of the perspectives for the discovery of wealth of understanding of everything that the human person is involved in and of the world he resides in, creates and converts to his own needs. The considerations in the text stress the importance of human reflection,ability to retrace feelings in the individual biography and of being able to interpret one’s own experiences. Presenting these considerations in the biographic-narrative orientation reveals the essence of understanding of the issues discussed in the article from the perspective of the experiencing subject.